PELUANG BISNIS ONLINE SITUS VOUCHER DISKON - Halawa, Fransiscus Amonio (Universitas Bunda Mulia, 2018)
ABSTRACT Discount voucher / voucher sites are one part of e-commerce. Rampant discount sites in Indonesia, a separate phenomenon, especially in terms of the development of Internet-based commerce (e-commerce). Discount voucher sites are sites or mobile apps that market advertisements about promos and discounts being held by companies into the world of the internet so that the spread becomes more widespread. With a discount voucher site, companies can advertise their promotions and discounts to the internet. The methodology of data collection is done by observation, namely: direct observation on various voucher and discount voucher sites in Indonesia and with Library Studies, reading books, articles and sites that can assist in the analysis. For marketing strategy done with Organic Marketing, that is by using SEO (Search Engine Optimization) Hash Tags, Meta Tags, Achor Links that must be applied into the website, outside of the side of the website, organic marketing can also be done by way of broadcasting and social media press. For offline marketing channels, discount voucher sites can be made by distributing flyers to public places, such as malls, to inform the public that there is a discount voucher Site presence that they can download using a smartphone. Business analysis is carried out by assessing business feasibility studies in terms of financial aspects. Based on the calculation of investment feasibility study, by using the method of payback period, net present value, internal rate of return, and profability index, it can be concluded that discount voucher sites deserve to be a business opportunity. Keywords : E-commerce, Discount Vouchers, Investment Feasibility Study